2006
DOI: 10.1007/s10750-005-1949-8
|View full text |Cite
|
Sign up to set email alerts
|

Predation of Northern Pike (Esox lucius L.) Eggs: A Possible Cause of Regionally Poor Recruitment in the Baltic Sea

Abstract: Northern pike (Esox lucius) spawning habitat and egg mortality were studied in three spawning areas in 2001 along the Swedish coast of the Baltic proper: the Blekinge Archipelago, Kalmar Sound and coastal freshwater streams. Spawning peaked during the last week of April in streams, at temperatures ranging from 7.7 to 8.9°C and during the first week of May in brackish waters, at temperatures ranging from 8.9 to 13.8°C. Spawning occurred in shallow waters, at depths between 0.2-1.5 m, but generally most of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 25 publications
(31 reference statements)
2
48
0
Order By: Relevance
“…This is confirmed by small-scale experimental exclusion of larger fish and grazers, showing that declines in larger predators-by inducing a four level trophic cascade-increase filamentous algal growth with rates comparable to those caused by nutrient enrichment alone Sieben et al 2011b). Food competition and egg predation by the high abundances of stickleback may now even contribute to decreased recruitment success of perch and pike (Nilsson 2006;Ljunggren et al 2010), and potentially ''lock'' the coastal food web in an alternative, mesopredator-dominated regime. Thus, overfishing of offshore cod populations may have contributed to a shift in nearshore food web structure.…”
Section: Increase Of Mesopredatorsmentioning
confidence: 69%
“…This is confirmed by small-scale experimental exclusion of larger fish and grazers, showing that declines in larger predators-by inducing a four level trophic cascade-increase filamentous algal growth with rates comparable to those caused by nutrient enrichment alone Sieben et al 2011b). Food competition and egg predation by the high abundances of stickleback may now even contribute to decreased recruitment success of perch and pike (Nilsson 2006;Ljunggren et al 2010), and potentially ''lock'' the coastal food web in an alternative, mesopredator-dominated regime. Thus, overfishing of offshore cod populations may have contributed to a shift in nearshore food web structure.…”
Section: Increase Of Mesopredatorsmentioning
confidence: 69%
“…In most areas of the Baltic Sea including the Danish straits, commercial catches of pike have declined considerably since the 1970s-1980s suggesting a drastic population decrease (Nilsson et al, 2004;Nilsson, 2006;Lehtonen et al, 2009;Ljungren et al, 2010). Reasons for these declines in the different areas are not well determined, whether due to poor recruitment, habitat deterioration, eutrophication or other reasons.…”
Section: Implications For Managementmentioning
confidence: 99%
“…The spawning period lasted until the end of April. Nilsson [38] investigated the spawning areas of pike along the Swedish coast of the Baltic Proper and noted that spawning peaked during the last week of April in streams and during the first week of May in brackish waters. Treasurer [39] reported that in two Scottish lakes, Kinord and Davan, the spawning of fishes occurred in the first two weeks of April.…”
Section: Discussionmentioning
confidence: 99%